2021
DOI: 10.3389/fonc.2021.643394
|View full text |Cite
|
Sign up to set email alerts
|

Long Non-Coding RNA LINC00467 Correlates to Poor Prognosis and Aggressiveness of Breast Cancer

Abstract: Breast cancer remains the leading cause of female cancer-related mortalities worldwide. Long non-coding RNAs (LncRNAs) have been increasingly reported to play pivotal roles in tumorigenesis and cancer progression. Herein, we focused on LINC00467, which has never been studied in breast cancer. Silence of LINC00467 suppressed proliferation, migration, invasion and epithelial-to-mesenchymal transition (EMT) of breast cancer cells in vitro, whereas forced expression of LINC00467 exhibited the opposite effects. Fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 41 publications
(62 reference statements)
0
11
0
Order By: Relevance
“…LINC00467 is significantly upregulated in non-small cell lung cancer, promotes tumor cell growth and metastasis, and is related to clinical stage and poor prognosis [ 62 ]. It also promotes the proliferation, migration, invasion, and epithelial-mesenchymal transition (EMT) of breast cancer cells, tumor growth and lung metastasis in vivo, and high expression predicts poor OS [ 63 ]. In renal clear cell carcinoma, higher levels of LINC00997 are associated with lower OS and disease-free survival [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…LINC00467 is significantly upregulated in non-small cell lung cancer, promotes tumor cell growth and metastasis, and is related to clinical stage and poor prognosis [ 62 ]. It also promotes the proliferation, migration, invasion, and epithelial-mesenchymal transition (EMT) of breast cancer cells, tumor growth and lung metastasis in vivo, and high expression predicts poor OS [ 63 ]. In renal clear cell carcinoma, higher levels of LINC00997 are associated with lower OS and disease-free survival [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…LINC00467 could down-regulate miR-138-5p through functioning as a molecular sponge for this miRNA. Moreover, LINC00467 could enhance expression of LIN28B through directly interacting with it [6]. Another in silico study in breast cancer has shown possible role of LINC00467 in the regulation of peroxisomal lipid metabolism and immune response through targeting miRNAs [7].…”
Section: Sponging Effects Of Linc00467mentioning
confidence: 99%
“…Additional experiments have revealed that LINC00467 sponges miR-138-5p while directly interacting with LIN28B, a significant oncogene in breast cancer, to elevate its protein level. ( Zhang et al, 2021 ).…”
Section: Molecular Mechanism Of Linc00467 In Diverse Human Cancersmentioning
confidence: 99%